2018
DOI: 10.1167/iovs.18-24106
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Individual Disease Conversion in Early AMD Using Artificial Intelligence

Abstract: Artificial intelligence with automated analysis of imaging biomarkers allows personalized prediction of AMD progression. Moreover, pathways of progression may be specific in respect to the neovascular/atrophic type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
164
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 175 publications
(173 citation statements)
references
References 31 publications
6
164
0
3
Order By: Relevance
“…48 Schmidt-Erfurth et al found that drusen area was an important quatitative feature for progression. 16 Higher drusen volume was related to advanced AMD in a retrospective review by Lei et al, but other OCT parameters were more strongly related in their cases. 23 A combination of drusen parameters along with other OCT derived parameters such as hyperreflective foci and retinal thickness may be the most informative and predictive of progression.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…48 Schmidt-Erfurth et al found that drusen area was an important quatitative feature for progression. 16 Higher drusen volume was related to advanced AMD in a retrospective review by Lei et al, but other OCT parameters were more strongly related in their cases. 23 A combination of drusen parameters along with other OCT derived parameters such as hyperreflective foci and retinal thickness may be the most informative and predictive of progression.…”
Section: Discussionmentioning
confidence: 87%
“…SD-OCT can quantify variation in morphology in a way that is accurate and reproducible. Other AMD phenotypes detectable on OCT including subfoveal fluid, retinal and choroidal thickness, retinal hyperreflective foci, other drusen characteristics such as hyper-reflectivity and homogeneity, are opportunities for exploration in the context of subtyping AMD and assessing risk of progression, 15,16,23,48 as well as defining the associations with genetic variants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations